Efficacy and safety of Xiongzhitongluo granules in the treatment of acute ischemic stroke: study protocol for a randomized controlled trial - Yunmeng Chen; Jingjing Wei; Xiao Liang; Yue Liu; Lina Miao; Di Zhao; Yunfan Zhang; Hongxi Liu; Yunling Zhang (Frontiers in Medicine)
IntroductionAcute ischemic stroke (AIS) poses a significant risk to human health. Intravenous thrombolysis and mechanical thrombectomy are essential treatments for AIS, offering substantial benefits for neurological recovery and brain protection. However, their efficacy is often limited by stringent time constraints and contraindications, restricting accessibility for certain patient populations. Investigating novel therapeutic strategies is, therefore, crucial. Our team developed Xiongzhitongluo granules specifically for AIS and is conducting a randomized controlled trial (RCT) to validate their effectiveness.Methods and analysisThis multi-center, randomized, double-blind, placebo-controlled clinical trial includes 120 participants randomly allocated to the intervention or placebo group. Participants will receive a 14-day treatment alongside routine medications and will be monitored at multiple time points: days 1, 3, 5, 7, 14, 30, 60, and 90. The primary outcome is the change in the National Institutes of Health Stroke Scale (NIHSS) score from baseline to day 14. Secondary outcomes include the Scandinavian Stroke Scale (SSS), Barthel Index (BI), modified Rankin Scale (mRS), Brief Mini-Mental State Examination (MMSE), and traditional Chinese medicine (TCM) symptom assessment. Safety evaluations will include vital signs and laboratory tests. Data will be recorded using Epidata V3.1 and analyzed with SPSS 26.0.Ethics and disseminationThis study received approval from the Ethics Committee of Xiyuan Hospital, China Academy of Chinese Medical Sciences (2021XLA102-2). Written informed consent was obtained from all participants.Clinical trial registrationhttps://clinicaltrials.gov/, identifier, ChiCTR2200061859.